(18)F-FET MicroPET and MicroMRI for Anti-VEGF and Anti-PlGF Response Assessment in an Orthotopic Murine Model of Human Glioblastoma - Nedergaard, Mette Kjoelhede (PLoS One, 2015)
BACKGROUND: Conflicting data exist for anti-cancer effects of anti-placental growth factor (anti-PlGF) in combination with anti-VEGF. Still, this treatment combination has not been evaluated in intracranial glioblastoma (GBM) xenografts. In clinical studies, position emission tomography (PET) using the radiolabeled amino acid O-(2-(18)F-fluoroethyl)-L-tyrosine ((18)F-FET) and magnetic resonance imaging (MRI) add complementary but distinct information about glioma growth; however, the value of (18)F-FET MicroPET combined with MicroMRI has not been investigated preclinically. Here we examined the use of (18)F-FET MicroPET and MicroMRI for evaluation of anti-VEGF and anti-PlGF treatment response in GBM xenografts. METHODS: Mice with intracranial GBM were treated with anti-VEGF, anti-PlGF + anti-VEGF or saline. Bioluminescence imaging (BLI), (18)F-FET MicroPET and T2-weighted (T2w)-MRI were used to follow tumour development. Primary end-point was survival, and tumours were subsequently analysed for Ki67 proliferation index and micro-vessel density (MVD). Further, PlGF and VEGFR-1 expression were examined in a subset of the xenograft tumours and in 13 GBM patient tumours. RESULTS: Anti-VEGF monotherapy increased survival and decreased (18)F-FET uptake, BLI and MVD, while no additive effect of anti-PlGF was observed. (18)F-FET SUV(max) tumour-to-brain (T/B) ratio was significantly lower after one week (114±6%, n = 11 vs. 143±8%, n = 13; p = 0.02) and two weeks of treatment (116±12%, n = 8 vs. 190±24%, n = 5; p = 0.02) in the anti-VEGF group as compared with the control group. In contrast, T2w-MRI volume was unaffected by anti-VEGF. Gene expression of PlGF and VEGFR-1 in xenografts was significantly lower than in patient tumours. CONCLUSION: (18)F-FET PET was feasible for anti-angiogenic response evaluation and superior to T2w-MRI; however, no additive anti-cancer effect of anti-PlGF and anti-VEGF was observed. Thus, this study supports use of (18)F-FET PET for response evaluation in future studies.